The relationship between rewords and employee's motivation among employees at Tenaga Nasional Berhad, Jitra, Kedah Darul Naim / Nur Zuraihan Mohd Zahir - Mohd Zahir, Nur Zuraihan (2014)
The aim of this study is to identify the relationship between rewards and employee's motivation among permanent worker at Tenaga Nasional Berhad (TNB) Jitra, Kedah Darul Aman. The selection of respondents will be based on stratified sampling where the respondents had been choosing randomly among the worker in TNB Jitra. The list of departments including staffs working under their department has been given by the administrative assistant of record department. In this study, questionnaire is used as data instruments for data collection. There are three sections in the questionnaire. In section A, the respondents are needed to provide information regarding their demographic profile such as gender, age, educational level and length of services in the organization. For section 8, respondents required to answer the questions relate to rewards which are focused on bonus and promotion.